Examining service triad operations: Formation, functioning, and feedback exchanges - Suurmond, Robert; Menor, Larry J.; Wynstra, Finn (Production and Operations Management, 2022)
We study service triads by examining the member‐to‐member exchanges underpinning service formation, functioning, and feedback. A service triad comprises two serviced customers from the supplier's standpoint and two service providers from the end user's standpoint, which can cause operational complexity and challenges. We view the service triad as an operating entity and study four information‐rich cases to improve our understanding of this operational complexity. Leveraging scholarly knowledge related to service operations management and ecosystems theory, we uncover several interesting patterns related to the formation, functioning, and feedback exchanges. First, the formation exchanges depend on the value creation goal of the service triad. Second, the service buyer engages in operational coordination, despite delegating the delivery of services to the supplier. Third, feedback exchanges allow the service triad to monitor service performance for further improvement and innovation. Our qualitative inquiry focusing on the visualization and codification of members’ participation in exchanges advances our collective understanding of service triads beyond the dominant focus on structure and governance.